2020
DOI: 10.1177/0954406220960772
|View full text |Cite
|
Sign up to set email alerts
|

Multi sensor based strategies for accurate prediction of friction stir welding of polycarbonate sheets

Abstract: High performance thermoplastic is often used in automotive and aerospace sectors. Friction stir welding (FSW) has been a suitable method for joining these thermoplastic materials. However, the process characteristics vary dynamically, even at same parametric conditions due to process disturbances. While quite a few studies have been reported in experimental investigation, the usage of sensors for the process monitoring during welding has not been explored. Therefore, the present paper focuses on various sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Thus, it may be concluded that there was an axial thrust force reduction with more torque requirement at high tool rotational speeds as noticed in previous works. 13,23,24,27 However, the thrust force with respective torque reduction was more predominant for PC and N6, respectively.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, it may be concluded that there was an axial thrust force reduction with more torque requirement at high tool rotational speeds as noticed in previous works. 13,23,24,27 However, the thrust force with respective torque reduction was more predominant for PC and N6, respectively.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 94%
“…The weld peak temperature is the highest temperature of the weld thermal cycle which comprised of heating and followed by cooling of the weld bead. The weld cooling rate that is, the slope of weld cooling curve just after welding has been determined at 25 second (s) later just after reaching weld peak temperature time 24,26 that is, weld peak temperature to instantaneous temperature at 25 s intervals after reaching peak temperature, which may be expressed as…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that the frequency spectrum of forces could be used for detection of defects. According to the research reported by Sahu et al [ 15 ], compared with the temperature signals measured by K-type thermocouples, the axial force better predicted the tensile strength. Boldsaikham et al [ 16 ] used discrete Fourier transform and a multi-layer neural network to analyze the force signal, and proposed a nondestructive testing method for tunnel defects in the FSW process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, multi-sensor based process monitoring and weld quality prediction have been proposed in arc welding 29 as well as friction welding techniques. 30 Thus, the tool assisted axial thrust with material stirring torque during friction stir welding are extremely important for altered parametric conditions in thermoplastic polycarbonate 30 and different tool tilt angles in aluminium alloys. 31 The average axial pressure is higher during tool pin plunging over shoulder plunging due to higher frictional heat generation in FSW of polycarbonate.…”
Section: Introductionmentioning
confidence: 99%